STRATEGI DAKWAH PIMPINAN PONDOK PESANTREN AL-IKHLAS DALAM MENGEMBANGKAN SUMBER DAYA MANUSIA SANTRI DI DESA UJUNG KECAMATANDUA BOCCOE KABUPATEN BONE (Fakultas Dakwah dan Komunikasi, 2021)
The main problem in this study is the role of the head of Al-Ikhlas boarding school in developing Santri Human Resources in Ujung Village of Sub-District Two Boccoe Bone District and presenting substance problem which is how the form of da'wah strategy applied in developing santri resources? The main problem in this study is the role of the head of Al-Ikhlas boarding school in developing Santri Human Resources in Ujung Village of Sub-District Two Boccoe Bone District and presenting substance problem which is how the form of da'wah strategy applied in developing santri resources? What are the obstacles of al-Ikhlas boarding school leadership in developing human resources in the village at the end of the district two boccoe bone district? What are the obstacles of al-Ikhlas boarding school leadership in developing human resources in the village at the end of the district two boccoe bone district? This type of research is a qualitative research that in its data collection uses the method of dawah management approach. This type of research is a qualitative research that in its data collection uses the method of dawah management approach. The data sources in this study have two sources namely primary data sources of six people and secondary data sources, through the data collection methods used are observation, interview, and documentation. The data sources in this study have two sources namely primary data sources of six people and secondary data sources, through the data collection methods used are observation, interview, and documentation. Data collection and data analysis techniques use various stages, namely, data reduction, data collection, and conclusion drawing. Data collection and data analysis techniques use various stages, namely, data reduction, data collection, and conclusion drawing. The results of this study show that al-Ikhlas boarding school in developing students, namely in the field of education, personality, da'wah, rewarding, extracurricular, giving punishment. The results of this study show that al-Ikhlas boarding school in developing students, namely in the field of education, personality, da'wah, rewarding, extracurricular, giving punishment. The problem is also there to the internal boarding school al-Ikhlas itself such as, pembina, santri that can hinder the process of human resource development in the Islamic boarding school of al-ikhlas in the village end of Dua Boccoe district bone regency. The problem is also there to the internal boarding school al-Ikhlas itself such as, pembina, santri that can hinder the process of human resource development in Pondok pesantren al-ikhlas in the village end of Dua Boccoe district bone regency. The research is a strategy of dawah in developing human resources santri can be further improved so that students are more qualified and have good morals according to the teachings of Islam specific in the boarding school in the village end of Dua Boccoe district bone district.